Epsodic paroxysmal hemicrania with seasonal variation: case report and the EPH-cluster headache continuum hypothesis - Veloso Germany Gonçalves (Arquivos de Neuro-Psiquiatria, 2001)
Episodic paroxysmal hemicrania (EPH) is a rare disorder characterized by frequent, daily attacks of short-lived, unilateral headache with accompanying ipsilateral autonomic features. EPH has attack periods which last weeks to months separated by remission intervals lasting months to years, however, a seasonal variation has never been reported in EPH. We report a new case of EPH with a clear seasonal pattern: a 32-year-old woman with a right-sided headache for 17 years. Pain occurred with a seasonal variation, with bouts lasting one month (usually in the first months of the year) and remission periods lasting around 11 months. During these periods she had headache from three to five times per day, lasting from 15 to 30 minutes, without any particular period preference. There were no precipitating or aggravating factors. Tearing and conjunctival injection accompanied ipsilaterally the pain. Previous treatments provided no pain relief. She completely responded to indomethacin 75 mg daily. After three years, the pain recurred with longer attack duration and was just relieved with prednisone. We also propose a new hypothesis: the EPH-cluster headache continuum.